The Early Medieval Barrows with Kerbstones at the Leśnictwo Postołowo Site 11 in the Białowieża Forest (Szczekotowo Range) - Olczak, Hanna; Krasnodębski, Dariusz; Szlązak, Roman; Wawrzeniuk, Joanna (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2020)
In the western part of the Białowieża Forest, on the grounds of the Szczekotowo Range, one can find one of the largest and most interesting Early Medieval sepulchral complexes in the Middle Bug River basin. One part of it is the cemetery at Leśnictwo Postołowo Site 11, which includes five burial mounds surrounded by settings of kerbstones. In a barrow, which was excavated in 2017, an inhumation burial of a woman dating back to the 12th century and equipped with a necklace of glass beads was discovered. This site is another excavated cemetery from the Białowieża Forest area, where – in contrast to other regions of the Upper Narew and Middle Bug River basins – the barrow was the most common type of grave in the younger phase of the Early Middle Ages. This article presents various aspects of the investigated burial, which undoubtedly casts new light on our knowledge about the Mazovian-Rus’ cultural borderland during the period of state formation
ill. ; 25 cm
Keywords: Białowieża Forest; early Middle Ages; barrow cemeteries; Mazovian-Rus’ borderland